Perlindungan Konsumen Terhadap Korban Penipuan Online Jual Beli Pakaian Bekas Impor (Thrifting) - Permana, Abdullah Marshal (Proceedings Series on Social Sciences & Humanities, 2024)
With the rapid development of technology day by day, buying and selling clothes can be done in various ways and through various media platforms. Thrifting or buying and selling used imported clothes is an activity that is currently being carried out by people all over the world. They prefer to buy imported second-hand clothing, because they consider the price and quality to be very affordable for their pockets. In the sale of imported used clothing, many thrift markets exist and exist in Indonesia and in other countries. People usually look for or hunt for the goods they are looking for in the market by looking at the condition of the goods, and negotiating prices directly with the sellers themselves. In this way, buyers can be satisfied with the goods they buy because they see the goods they buy directly. As technology develops, buying and selling is done via online media, where buyers are very limited in seeing the goods they want to buy. Buyers can only see photos or images on online media. Sometimes sellers do not list the shortcomings of the item. With this, many individuals are looking for illegal money by committing fraud through online sales. They look for loopholes by taking advantage of the trend of buying and selling which is currently busy, many ordinary people easily believe in this buying and selling.